Pre- and post-sentence mental health service use by a population cohort of older offenders (≥45 years) in Western Australia - Sodhi-Berry, N.; Knuiman, M.; Alan, Janine; Morgan, V.; Preen, D. (Springer Medizin, 2015)
Purpose - Information on older offenders’ mental health service (MHS) used before and after sentence is sparse. We therefore aimed to determine the 1-year prevalence of MHS use before sentence, and the likelihood and predictors of MHS use in the 5-year post-sentence period by first-time older adult offenders (≥45 years). Methods - Pre- and post-sentence MHS use by a cohort of 1,853 first-time offenders over 45 years in Western Australia was determined through whole-population linked administrative data. Logistic regression models compared the 1-year pre-sentence MHS contacts between offenders and matched non-offenders. Cox proportional hazards regression models identified the socio-demographic, offending and pre-sentence health service variables that determined post-sentence MHS use. Results - Older offenders were six times more likely to have used MHSs than non-offenders before sentence. Substance use was the most commonly treated disorder. Non-custodial offenders were twice more likely than prisoners to have been treated for any mental disorder and substance use disorders, and violent offenders were four times more likely to have attempted self-harm than non-violent offenders before being sentenced. The strongest predictors of post-sentence MHS contact were past psychiatric diagnosis in offenders with a pre-sentence MHS contact, and pre-sentence hospitalisation for attempted self-harm or physical illness, or being a male in those without. Discontinuity in MHS use after sentence by over half of the offenders with a prior contact was prominent. Conclusion - Better detection and treatment of mental disorders in older offenders to ensure continuity of care at all transition points through age-sensitive correctional and community-based MHSs is needed.